Developmental plasticity of Arabidopsis hypocotyl is dependent on exocyst complex function - Janková Drdová, Edita (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.